Pengaturan Sanksi Hukum Terhadap Pemilikan Rumah Tempat Tinggal Bagi Orang Asing di Indonesia - Dewik Kusumawati (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2019)
Investment / investment made by foreigners in Indonesia, requires the availability of land in the form of land for their business needs. The very limited availability of land and very high land requirements need to be regulated so that it does not cause problems in the future, can provide legal certainty, justice, and benefit everyone and also foreigners who invest in Indonesia. This research aims to find out and analyze the regulations regarding the legal basis regarding Residence Ownership or Residential Functioning as a Usage Place according to Government Regulation Number 103 of 2015 concerning Housing or Residential Houses by Foreigners Domiciled in Indonesia. and to find out and analyze the regulation of sanctions provisions for foreigners who violate the rules regarding residential or residential housing in Indonesia. The research method used in this research is Juridical-Normative research method. The research approach used by the author is a legal approach, conceptual approach, analytical approach, and philosophical approach. The results of this research are the conflicting norms / norm conflicts regarding the Agreement on Separation of Property contained in PP 103/2015 in contravention of the existing regulations in the LoGA and Law No.1 of 1974 concerning Marriage (hereinafter abbreviated as Marriage Law), as well as norm conflicts / norm conflict regarding the period of use rights contained in PP 103/2015 with the provisions in PP 40/1996. While the regulation of sanctions for foreign nationals who violate the legal provisions regarding the ownership of residential or residential houses in Indonesia is regulated in Article 26 paragraph (2) of the LoGA. The Government should evaluate the policy regarding housing for foreigners, in order to achieve the legal objectives of justice, benefit and legal certainty for the community. Penanaman Modal/Investasi yang dilakukan oleh WNA di Indonesia, memerlukan ketersediaan lahan berupa tanah untuk keperluan usahanya. Ketersediaan tanah yang sangat terbatas dan kebutuhan tanah yang sangat tinggi perlu diatur agar tidak menimbulkan masalah dikemudian hari, dapat memberikan kepastian hukum, keadilan, dan bermanfaat bagi semua orang dan juga bagi Orang Asing yang berinvestasi di Indonesia. Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaturan mengenai dasar hukum mengenai Pemilikan Rumah Tempat Tinggal atau Hunian difungsikan sebagai Tempat Usahamenurut Peraturan Pemerintah Nomor 103 tahun 2015 tentang Pemilikan Rumah Tempat Tinggal atau Hunian oleh Orang Asing yang Berkedudukan di Indonesia. serta untuk mengetahui dan menganalisis pengaturan ketentuan sanksi bagi Warga Negara Asing yang melanggar aturan mengenai Pemilikan Rumah Tempat Tinggal atau Hunian di Indonesia. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian Yuridis-Normative. Pendekatan Penelitian yang digunakan oleh penulis adalah pendekatan undang-undang, pendekatan konsep, pendekatan analitis, dan pendekatan filosofis. Hasil dari penelitian ini adalah Pertentangan norma/konflik norma tersebut mengenai Perjanjian Pemisahan harta yang ada dalam PP 103/2015 bertentangan dengan pengaturan yang ada pada UUPA dan Undang-undang No.1 tahun 1974 tentang Perkawinan (selanjutnya disingkat UU Perkawinan), serta pertentangan norma/konflik norma mengenai jangka waktu Hak Pakai yang terdapat dalam PP 103/2015 dengan ketentuan yang ada pada PP 40/1996. Sedangkan pengaturan sanksi bagi Warga Negara Asing (WNA) yang melanggar ketentuan hukum mengenai Pemilikan Rumah Tempat Tinggal Atau Hunian di Indonesia, diatur dalam Pasal 26 ayat (2) UUPA. Hendaknya Pemerintah mengevaluasi kebijakan mengenai rumah tempat tinggal bagi orang asing, demi mencapai tujuan hukum yaitu keadilan, kemanfaatan dan kepastian hukum bagi masyarakat.